Efforts to Improve Se-Enak Dampling (Child Mental Health Impact of Bullying) in SD Negeri Citali, Pamulihan District - Hana Fitria Andayani; Aditya Maulana; Dewita Purwati; Dini; Fitri Novianti Nurfadhilah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Bullying is any form of violence carried out intentionally by one person or group of people who are more powerful or powerful against others, with the aim of hurting and carried out continuously. Bullying cases often occur in the school environment including in the elementary school environment, where this bullying case must have a bad impact on children's mental health. The purpose of counseling at SD Negeri Citali Pamulihan District is so that students can understand the meaning of what is meant by bullying, types of bullying, know the causes of bullying, know the effect of bullying on mental health, can know the basic laws of bullying in children and of course they know about how to prevent and deal with bullying. This community service will be carried out in October 2023, with the focus of its activities being to provide knowledge to female students. Students do a pretest before being given counseling material which is carried out offline, then after being given counseling material students are given again post-test questions with the aim of providing an overview of children's knowledge about bullying. With the hope that after this counseling activity, students of SD Negeri Citali can increase their knowledge about bullying and its impact on their mental health